Determinan Penggunaan Metode Kontrasepsi Jangka Panjang Implan Pada Pasangan Usia Subur : A Determinants of The Use Long-Term Implant Contraceptive Methods Among Couples of Childbearing Age - Ernawati, Ernawati; Sumarmi, Sumarmi; Mantasia, Mantasia; Nuryana, Riska (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Background: to determine the factors that influence the use of contraceptive implants in couples of childbearing age in Mata Allo village, Gowa Regency in 2023. Research Method: The type of research is qualitative research with a sectional study approach. This research was conducted in Mata Allo village, Gowa Regency with a population of 253 active family planning acceptors. A total of 72 samples were taken with the collection technique used was Propability Sampling with Simple Random Sampling technique. Data processing was used computerized with the SPSS version 24.0 program. Data analysis used chi square test analysis. This research used primary and secondary data and was presented in the form of tables and narratives. Results: There is no significant relationship between age and use of implants with a p-value of 0.886. There is a significant relationship between parity and implant use with a p-value of 0.006. There is a significant relationship between knowledge and use of implants with a p-value of 0.000. There is a significant relationship between husband's support and use of implants with a p-value of 0.000. Discussion: It is hoped that family planning acceptors can enrich information to increase knowledge about contraceptive methods that are suitable for use, in each acceptor's condition.